The Infrastructure Development Compatibility To Enhance Community Welfare - Asfar, Ali; Zauhar, Soesilo; Rochmah, Siti; Hermawan, Hermawan (FIA UB, 2021)
This paper aims to describe and analyze the regulations, the interest of actors and the budgets compatibility between the central government, regional governments in infrastructure development of Rokan Hilir District. This research uses a descriptive approach, with qualitative research methods. The research findings show that there is no compatibility between the regulations of the central government and regional governments, therefore the regulations made by the central government cannot be carried out effectively and there are also conflicts with the wishes of local communities. The central government prioritizes the interests of the country as a whole rather than the interests of the people in the region. Infrastructure development in Rokan Hilir Regency is strongly influenced by the Executive Actor and Political Actor (Legislative). The 2012 fiscal year to 2017 indicated that the operating budget is greater than the development budget, this is happened due to the siphoning of the budget to pay the salaries of temporary workers, and other routine expenditures. The implication is that Rokan Hilir Regency unable to carry out some physical development (infrastructure).